PRIORITIZATION OF MULTILATERAL AGREEMENTS ON EXPORT CONTROL OF DEFENSE PRODUCTS AND SENSITIVE TECHNOLOGIES BY HIERARCHICAL ANALYSIS PROCESS - Gaviao, Luiz Octavio; Dutra, Luciano Dias; Kostin, Sergio (AUSTRAL: Brazilian Journal of Strategy & International Relations, 2022)
This paper proposes a model to support the decision to choose which multilateral export control regime of defense products and sensitive technologies in which Brazil does not yet participate, namely, Wassenaar Arrangement, Australia Group and Zangger Committee, should be prioritized for adhesion. For the development of this model, the Analytic Hierarchy Process (AHP) method was used, considered adequate for solving problems where criteria are qualitative and decisions tend to be based on personal experiences. The hierarchical structure of the problem used seven criteria (Country Legislation, Regulatory System, Licensing Structure, Enforcement Capacity, International Cooperation, Costs of Adhesion and Benefits for the Defense Industrial Base) to compare the three mentioned agreements. A questionnaire was set up and specialists related to National Defense were selected to answer them, after which their answers were collected, standardized, processed and analyzed. At the end, the agreements were ordered by preference to support decision making, illustrating the application of the proposed model.